﻿The genus Tegostoma in Armenia, with description of a new species (Crambidae, Odontiinae) - Jan Šumpich; Ole Karsholt; Nikolay Savenkov; Hartmut Roweck (Nota Lepidopterologica, 2022)
A small but beautifully coloured species of Tegostoma Zeller, 1847, which was collected by the authors in Armenia, has turned out to be unnamed and is here described as Tegostoma burtoni sp. nov. The description is supported by morphology and DNA barcodes . Photographs of the adults and genitalia of both sexes are provided. Tegostoma lepidalis (Herrich-Schäffer, 1851) and Pyrausta gulpembe Kemal & Koçak, 2018 are recorded as new species for Armenia.